Comparison Results of Islamic Education Learning Using Teams Games Tournament (TGT) in Indonesia and Thailand. (July 2018) - Hidayat, Mohammad Sadid; Kadir, Abdul; Herman
Abstract: The purpose of this study is to know; 1) the learning result of the students of Islamic religion lessons in Indonesia in the implementation of Team Game Tournament (TGT), 2) the learning result of the students of Islamic religion lesson in Thailand in the implementation of Team Game Tournament (TGT), and 3) the difference of students in Indonesia and Thailand in the implementation of Team Game Tournament (TGT). This research uses an experimental method with post-test group design. The research was conducted in Indonesia and Thailand. The sample of research in Indonesia is the students of Senior High School 01 Kendari, Southeast Sulawesi province while research sample in Thailand is the student of Khamphee Witaya School of South Thailand Province. The research instrument is a valid and reliable post-test. The test material is faith in the angel of Allah. Data analysis techniques used descriptive and inferential statistical analysis. Inferential analysis using three tests is; Normality test using Kolmogorov-Smirnov Test, homogeneity test using Levine Test, and hypothesis test using t-test at 5% significance level by comparing significance probability value (ρ) with significance level (a) = 0, 05 using SPSS-20. The results of this study are: 1) the learning outcomes of the students of Islamic religion in Indonesia by using Team Game Tournament (TGT) is very good with an average score of 90.31, 2) the learning outcomes of Islamic religious lessons in Thailand using Team Game Tournament (TGT ) are is good with an average score of 83.12, and 3) there are differences in student learning outcomes in Islamic religious lessons in Indonesia and Thailand using Team Game Tournament (TGT), the difference is the result of learning in Indonesia is higher than the results of study in Thailand.